Proposed approaches to a programme of education for internationl understanding in primary teacher training institutions in Korea - Lee, Choul Il 1929- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1965)
This study is an initial investigation on the problem of Korea with regards to international understanding and therefore shows the serious need of education for international understanding from the historical background of Korea, a sound background philosophy of education for international understanding from the related literatures including the aims of Korean education, and the factors involved in establishing a programme of education for international understanding based on the needs, problems and potentials of the primary teacher education in Korea.
Thesis (Master of Education)--University of the Philippines Diliman
Keywords: International education; Education -- Korea